PERSPEKTIF GURU EFEKTIF PADA HASIL EVALUASI KINERJA PPL MAHASISWA - Muslih Muslihudin Muslih (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2023)
Kegiatan PPL sangat strategis untuk mengasah kemampuan calon guru. Kenyataannya kegiatan PPL belum mengacu kepada perspektif atau konsep kemampuan guru yang jelas dan terukur. Penelitian ini bertujuan mengetahui kinerja praktikan mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan (FITK) IAIN Syekh Nurjati Cirebon dalam kegiatan PPL di sekolah dengan menggunakan perspektif guru efektif sehingga model konseptual tentang program pesiapan PPL dapat disusun dan diberikan sebelum mahasiswa diterjunkan untuk mengikuti kegiatan praktek lapangan. Penelitian ini didesain secara kuantitatif dengan menggunakan metode penelitian evaluatif. Data diperoleh melalui dua kelompok respondents. Pertama, the respondents dari peserta PPL dipilih secara random sebanyak 36 orang untuk mengisi angket tentang keterampilan guru perspektif. Kedua, 80 responden dari guru pamong diberi angket tentang kinerja dan kompetensi praktikan perspektif guru efektif. Temuan penelitian menunjukan bahwa dari 5 aspek indikator guru efektif, 60% responden kurang efektif terkait komponen kepribadian; 65% belum efektif dalam mengelola kelas; 61.9% belum efektif dalam merencanakan pembelajaran; 62% belum efektif dalam melaksanakan pembelajaran; 66% belum efektif dalam memantau kemajuan siswa. Hasil penelitian ini dapat menjadi dasar untuk mengembangkan praktek pengalaman calon guru dengan mengacu kepada perspektif tertentu.Kata kunci: effective teaching, initial teacher training, training developmentÂ A Field Experience Practice activity is very strategic to develop the competence of prospective teachers. In fact, the Field Experience Practice have not referred to the perspective or concept of clear and measurable teacher competence. This study aimed to investigate the performance of practicing students of the Faculty of Tarbiyah and Teacher Training (FITK) IAIN Syeikh Nurjati Cirebon in the Field Experience Practice activity at schools using the perspective of effective teachers, so that a conceptual model of the Field Experience Practice preparation program can be developed and provided before students are deployed to follow field practice activities. This research was designed quantitatively using the evaluative research method. Data were obtained through two groups of respondents. First, the respondents from the participants of Field Experience Practice were randomly selected consisting of 36 people to fill out questionnaires about the skills of perspective teachers. Second, 80 respondents coming from mentor teachers were given questionnaires about the performance and participant competence of effective teacher perspectives. The findings show that of the 5 aspects of effective teacher indicators, 60% of respondents were less effective related to the personality component; 65% of respondents have not been effective yet in managing the classroom; 61.9% of the respondents have not been effective yet in planning lessons; 62% of the respondents have not been effective yet in implementing instruction; and 66% of the students have not been effective yet in monitoring student progress. The results of this study can serve as a basis for developing prospective teachers' experiential practices by referring to certain perspectives. Keys Word: effective teaching, initial teacher training, training development